Kemiskinan Nelayan Tradisional Bermula Dari Wilayah Penangkapan Ikan - Zulkifli Zulkifli; Agustrisno Agustrisno; Henry Sitorus (PERSPEKTIF, 2021)
This research is motivated by a contradictory reality about the life of traditional fishermen. Traditional fishermen have “sacred” zones for fishing activities which are protected by law due to their highest biodiversity and cultural importance to local fishing communities. On the other hand, 76 percent of the traditional fishermen are classified as poor; the level of poverty headcount index (PHI) reaches 32.4 percent. Based on this contradictory situation, 2 (two) important questions arise: what happens in the fishing area of traditional fishermen and whether the poverty experienced by traditional fishermen starst from this fishing ground. This research took place in Bagan Kuala, a village where the majority of the population are traditional fishermen. This study used an ethnographic approach with two data collection tools, which are interviews and observations. It was found that each traditional fisherman in this village has its own fishing grounds and boundaries. The boundary is marked by fish aggregating device (FAD), which also serve its purpose as fish catcher. Some of the FADs have been owned by fishermen for many generations. Outsiders often trespass this fishing ground, particularly at night where they use modern tools like trawl, destroying the fishermen’s FADs. As a result, there are conflicts and also negotiations involving the locals and outsiders who asked for their permission; the catch was divided depending on the agreement. From these findings, it can be concluded that poverty can start from the fishing ground.